Modelling of atmosphere remote sensing by the multi-wavelength Lidar : Application to real Signals. - DEBIAIS, GEORGES; GUGLIELME, VERONIQUE; GUEDJE, KOSSI FRANÇOIS (My University, 2008)
LIDAR is one of the cornerstones in the study of the atmosphere. In recent work, we developed a theoretical analysis of the atmosphere response to a monochromatic electromagnetic excitation, as function of altitude, by modelling in a specific way the response of clouds. That analysis established that the density of particles in the cloud can be adequately interpreted in terms of the Lorentzian probability distribution. Theoretical signals thereby generated, fitted with suitable parameters, reproduce the experimental data, making possible a characterisation of the atmosphere with the determination of its significant macroscopic and microscopic physical constants. In the present contribution, that study is refined by considering other relevant distribution laws susceptible to provide a better representation of the particle density as well as an improved model for the LIDAR response. More specifically, we use Rayleigh’s law to express the asymmetry sometimes observed in the cloud response. Furthermore, we suggest a theoretical reconstruction of the LIDAR signal which takes into account the influence of the wavelength on the mean free path of photons in the atmosphere.
Keywords: atmosphere; Lidar equation; clouds; scattering